Feeding habit of mantis shrimp, Miyakea nepa (Latreille, 1828) from coastal waters of Pantai Remis, Perak - Mat Noor, Nur Syuhada (2012)
Studies on feeding habit and diet preference by Miyakea nepa was conducted from March to July 2012. The study was done to examine feeding habit and types of food items and diet preference by M. nepa. The diets composition of M. nepa were examined based on 115 specimens taken from local fishermen in Pantai Remis, Perak. The diet composition were grouped into eight major categories consisted parts of shrimp, polychaete fragments, squid tissues, fish tissues, gastropods, shell fragments, eggs, and unidentified food items. In term of percentage, the most predominant prey items in the stomach of M. nepa were parts of shrimp (36.94%), followed by polychaete fragments (29.41%), fish tissues (14.1%), shell fragments (6.64%), squid tissues (5.28%), eggs (4.12%), unidentified food items (2.4%) and gastropods (1.58%). Shrimp is the most dominant food items ingested by M. nepa followed by polychaete worms and these both food items could be regarded as important diets for M. nepa. On the basis of food composition found in the stomach, it can be referred that M. nepa is carnivorous in feeding habit and feed on shrimp, polychaete, fish and squid.